The impact of entrepreneurship on college students’ innovative and entrepreneurial behavior under the influence of corona virus disease 2019 - Ran, Hong; Zhang, Meng; Mercado, Cecilia A. (Frontiers in Education, 2026)
This study investigates how COVID-19 pandemic has hindered the development of college students’ entrepreneurial skills. Focusing on three key traits-innovativeness, initiative, and risk-taking-this study applies cognitive-behavioral theory to analyze their impact on entrepreneurial willingness. Additionally, it evaluates the strength of this relationship by measuring how entrepreneurial spirit shapes intent. Key findings reveal varying effects across disciplines: major-specific differences in entrepreneurial intention (EI), innovation, initiative, and risk-taking scored 6.829, 1.718, 4.909, and 5.883, respectively. There is no significant connection between professionalism and innovativeness. Strong correlations emerged between environmental factors and entrepreneurial traits-initiative (0.659, p < 0.01), innovation (0.784, p < 0.01), risk-taking (0.677, p < 0.01), and willingness (0.643, p < 0.01). Among these, initiative and risk-taking exerted the greatest influence on willingness. Correlation analysis further confirmed entrepreneurship’s positive, statistically significant role in predicting intent. College students’ entrepreneurial willingness will therefore be enhanced by promoting entrepreneurship courses in institutions of higher learning to complement the development of an entrepreneurial spirit (ES).